Not All Oil Price Shocks Are Alike. A Replication Study of Kilian (American Economic Review, 2009) - Rich Ryan; Nyakundi Michieka (Journal of Comments and Replications in Economics (JCRE), 2025)
The price of oil can rise because of a disruption to supply or an increase in demand. The nature of the price change determines the dynamic effects. As Kilian (2009a) put it: "not all oil price shocks are alike." Using the latest available data, we extend Kilian's analysis using the R ecosystem and provide more evidence for Kilian's conclusions. Inference based on unknown conditional heteroskedasticity strengthens the conclusions. With the updated shocks, we assess how a local economy responds to the global oil market, an application that is relevant to policymakers concerned with the transition away from fossil fuels.Kern, Local labor market, Oil price, Real economic activity, Structural vector autoregression,, Unemployment rate, Vector autoregression
https://doi.org/10.15456/j1.2024244.2317598695
Keywords: E24; E31; E32; Q41; Q43; Q48; R23; 330; Kern; Local labor market; Oil price; Real economic activity; Structural vector autoregression; Unemployment rate; Vector autoregression